PENGEMBANGAN WEB PROFILE GEREJA SEBAGAI SARANA PELAYANAN KEAGAMAAN DI GMIT EBENHAEZER OEBA - Ledoh, Juan R M; Amos Pah, Clarissa Elfira; Mauko, Arfan Y; Taklal, Adi J; Wangge, Fajar A R; Fernando, Oswaldus P (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Gereja Masehi Injili di Timor (GMIT) Ebenhaezer Oeba Kupang uses information technology to support its business process. Although the church has social media accounts, they do not yet have a web profile that provides comprehensive information about the church. The reason for this is limited manpower. However, having an active web profile is essential for the church to share information and interact with the congregation and the community at large. To address the issue, it is suggested that the web profile of GMIT Ebenhaezer Oeba be revitalized. This revitalization aims to revive the web profile and add features that provide information and announcements to the congregation. This system can be accessed in real-time using a smartphone, laptop, or tablet connected to the internet. Through this system, the church can provide its identity and disseminate information needed by the congregation in a fast and timely manner.